PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU DALAM MENSTIMULASI TUMBUH KEMBANG BALITA DI PUSKESMAS SULEWANA KECAMATAN PAMONA UTARA KOTA POSO - Agustinus Talindong; Jumain (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2023)
Growth is related to the problem of changes in the size, number, size or dimensions of the cell, organ or individual level. Sulewana Health Center, North Pamona District, Poso City, the number of mothers who have toddlers is 1029, most of the mothers do not understand about the ability of mothers to practice in stimulating the growth and development of toddlers. The purpose of this study was to find out the effect of health education on mother's knowledge in stimulating toddler growth and development at the Sulewana Health Center, North Pamona District, Poso City. The type of research used in this research is quantitative, quasi-experimental pre and post test design. The knowledge dependent variable and the independent variable Toddler Growth and Development Data collection uses a questionnaire. The population in this study were mothers under five who were recorded at the Sulewana Health Center, North Pamona District, Poso City totaling 1029 toddlers, with a total sample of 20 people. The sampling technique used the Accidental Sampling method. The results of the univariate analysis showed that the results of the Wilcoxon test above showed a p value of 0.000, <(α0.05) so it can be concluded that there is an influence between mother's knowledge in stimulating the growth and development of toddlers in Health Education. The conclusion is that there is an effect of health education on mother's knowledge in stimulating the growth and development of toddlers in Health Education. Suggestions for other researchers can develop this research by taking themes such as forms of support in providing health education, with quantitative, qualitative or combined quantitative-qualitative research methods.